Beta Alúmina como conductor iónico: síntesis, procesamiento y caracterización funcional de la Beta Alúmina - Ruiz Madronero, Christhy (Editorial Académica Española, 2012)
El creciente desarrollo científico y tecnológico en el área de los materiales ha permitido abordar temas como el de los conductores iónicos de estado sólido, que son utilizados en la conformación de fuentes alternativas de energía, dadas las propiedades que presentan. Además, los dispositivos iónicos en Estado Sólido como baterías de alto rendimiento, celdas combustibles y de electrolisis, sensores químicos, convertidores termoeléctricos y celdas solares fotogalvánicas son de gran interés práctico en vista de su producción de energía y los requerimientos de control medio ambiental. El interés en la optimización de la conductividad iónica de la β-Alúmina radica en su aplicación como electrolito sólido en fuentes alternativas de energía, debido a su alta estabilidad química y física, a altas temperaturas, que la capacitan para conformar fuentes de poder.<br

Composite films based on salicylic acid-layered zinc hydroxide and polyvinyl alcohol: Preparation, characterization, properties and potential applications - Ruiz Madronero, Christhy; et al. (Polymer Testing, 2021)
Composite films of Polyvinyl alcohol (PVA) and hybrid materials based on salicylic acid –layered zinc hydroxide acetate (ZHA-SA) using zinc hydroxide acetate (ZHA) as host matrix were obtained by the casting method. The resulting composite films were characterized by FT-IR, X-ray diffraction, scanning electron microscopy (SEM) and atomic force microscopy (AFM) evidencing the incorporation of the layered materials in PVA matrix with relatively smooth and orderly surfaces. A significant reduction in the crystallinity of neat PVA film and a slight increase in transport coefficients of oxygen through the composite films have been observed. This behavior has been attributed to a high compatibility and adhesion between the fillers and polymeric matrix. Evaluation of the mechanical properties, in terms of stress, revealed that a low content of fillers (1.0 wt %) were able to increase the response of PVA composites by 63% with the addition of ZHA, and 45% with ZHA-SA. The results demonstrated the potential application of ZHA and ZHA-derived hybrid material in the preparation of multi-functional polymer composites to be used in packaging food system
Keywords: Hybrid material; Salicylic acid; Layered zinc hydroxide acetate; Poly(vinyl) alcohol Composite films; Reinforcement effect; Stress

Evaluación de la conservación de parámetros físicos en fresas envasadas con sistemas activos basados en polivinil-alcohol (PVOH) y materiales laminares funcionalizados con compuestos fenólicos - Ruiz Madronero, Christhy; et al. (2020)
En este trabajo, sistemas poliméricos compuestos basados en polivinil alcohol (PVOH) y estructuras laminares funcionalizadas de hidroxiacetato de zinc y ácido cafeico (ZHA y ZHA-CA) fueron analizadas como envases activos para evaluar su influencia en la conservación de parámetros físicos como firmeza, pérdida de peso y alteración de color superficial a fresas envasadas durante un periodo de almacenamiento de seis (6) días. Los resultados evidenciaron un efecto positivo en la retención de la firmeza en las fresas envasadas en sistemas poliméricos compuestos (PVOH/ ZHA y PVOH/ZHA-CA) en comparación con los resultados obtenidos para las películas de la matriz polimérica convencional, PVOH (control). De la evaluación del porcentaje de variación de la intensidad de color (%ΔC), y porcentaje de variación del brillo (%ΔL) de las fresas envasadas, los sistemas poliméricos compuestos permitieron mantener la calidad del color a diferencia de lo observado en las fresas envasadas con PVOH puro. A partir de estos resultados, los sistemas poliméricos compuestos evaluados pueden ser una prometedora opción para ser usados en el envasado de alimentos no solo por la bioactividad que ofrecen las cargas incorporadas sino también por las propiedades de bio-degradabilidad reportadas para la matriz polimérica de PVOH.<br
Keywords: Sistemas poliméricos compuestos; hidroxiacetato de zinc; polivinil alcohol; envases activos; fresas; firmeza; pérdida de peso; color superficial.

Evaluation of the electrical and dielectric behavior of hybrid materials based on layered zinc hydroxide and benzoate - Ruiz Madronero, Christhy; et al. (Ionics, 2019)
Benzoate anions were immobilized into layered zinc hydroxide nitrate (ZHN) via a soft chemistry method. The hybrid material was characterized by powder X-ray diffraction (PXRD), thermogravimetry (TG/DTA), differential scanning calorimetry (DSC) analysis, Fourier-transform infrared (FT-IR) spectroscopy, and impedance spectroscopy. The expansion of the interlayer space at 20.0 Å confirmed the incorporation of the benzoate forming bilayers into the layered structure. The interaction of the organic molecules occurs through the coordination of the carboxylate group to the Zn+2 atoms in the tetrahedral sites of the layered structure. The conductivity, ε′, and ε″ values of the hybrid materials were reduced five orders of magnitude in comparison with those of the inorganic ZHN host matrix at low frequencies. The results suggest that the solvation process between hydroxyl groups of the layers and adsorbed water molecules contributes in the electric response, whereas an induced dipole interaction describes the dielectric behavior of the hybrid material. The description of the electrical and dielectric properties can open new potentialities of this hybrid material for their possible application in electrochemical devices.<br
Keywords: Hybrid materials . Zinc hydroxide nitrate . Benzoate anion . Conductivity response . Dielectric properties

Fabrication, Characterization and Testing composite films of Poly(vinyl) Alcohol (PVOH)/ hybrid materials for potential use in strawberry packaging. - Ruiz Madronero, Christhy; et al. (A Complete Guide to Hybrid Materials, 2020)
Hybrid materials based on layered zinc hydroxide salts and phenolic compounds were incorporated into the polymer matrix of polyvinyl alcohol (PVOH) as fillers to form composite films using casting method. The structural, thermal, morphologic and compositional properties were studied in detail as a function of the hybrid material incorporated through X-Ray Diffraction (XRD), Thermogravimetric (TG) and Differential Scanning Calorimetry (DSC), Scanning Electronic Microscopy (SEM), Fourier transform infrared Spectroscopy (FT-IR) whereas the parameters of tensile strength and elongation at break from stress vs strain curves allowed to know the mechanical properties of the composite films. The conventional and exfoliated composites were obtained as consequence of the good dispersion and interaction through the H-bonds networks between the hybrid materials and polymer matrix due to the presence of the polar functional groups as –OH groups of the polymer, the crystallization water molecules, adsorbed water molecules and OH groups of phenolic acids in the hybrid materials. The good dispersion and interaction of the hybrid material and polymer matrix is supported with the reduction of the crystallinity on the composite films respect to that of the pure PVA films, which were obtained from DSC curves during the heating process. The estimated tensile strength evidenced an improvement of this parameter on the composite films with low content of filler (%w) in comparison with those values of the pure PVA films. The good dispersion of layered structure in the polymer matrix leads to an increase of stiffness of the composite films giving rise to the better response. The composite films from PVOH/Hybrid materials employed for the strawberries packaging during six days of storage under temperature and relative humidity conditions of relative humidity 17.3± 1 °C and 66 ± 2 % evidenced a positive effect on appearance, firmness retention and loss weight in comparison with those strawberries packaged in pure PVA films. Thus, the PVA/hybrid materials showed a beneficial effect on the conservation of strawberry quality in comparison with the pure PVA films that convert them in a promising option in food packaging with bioactivity properties.<br

Hybrid materials based on a layered zinc hydroxide solid and gallic acid: Structural characterization and evaluation of the controlled release behavior as a function of the gallic acid content - Ruiz Madronero, Christhy; et al. (Applied Clay Science, 2019)
The formation of hybrid compounds from gallic acid immobilized into a layered zinc hydroxide is reported. Elemental analysis, X-Ray diffraction, X-ray thermo-diffraction analysis, FT-IR spectroscopy, scanning electron microscopy, and X-Ray photoelectron spectroscopy allowed to identify clear differences between the hybrid materials obtained depending on the gallate anion content within the inorganic matrix. The elemental analysis showed a reduction in the zinc content while a lower d-value was exhibited in the XRD pattern for the material with the highest gallate anion content. With these results was evidenced a structural transformation from a Zn5(OH)8(NO3)2·2H2O type phase to a layered Zn3(OH)4(NO3)2 type phase when the gallate anions entirely replaced the nitrate anions. The formation of the latter phase at room temperature has not previously been reported. The final hybrid compound with a formula of Zn3(OH)4(C7H6O5)2, shows an interlayer space of 7.7 Å in comparison to 7.0 Å for the Zn3(OH)4(NO3)2 phase, which suggests an arrangement of the organic molecule with a parallel orientation to the y-axis. The X-ray diffraction patterns as a function of temperature showed that a completed incorporation of the gallate anion into the material increased over a 200 °C range (from 150 to 350 °C), the temperature for the decomposition of the layered phase to ZnO. The organic-inorganic materials synthesized using gallic acid as a guest and a layered zinc hydroxide as a host matrix can act as controlled delivery and storage systems. The release of gallate anions was found to be concentration-dependent with a release mechanism described by the Elovich and Freundlich models.<br

Preparation and Surface Functionalization of a Tunable Porous System Featuring Stacked Spheres in Cylindrical Pores - Ruiz Madronero, Christhy; Terlinden, Markus; Engelhardt, Matthias; Magnabosco, Giulia; Papastavrou, Georg; Vogel, Nicolas; Thommes, Matthias; Bachmann, Julien (Advanced Materials Interfaces, 2023)
A geometrically tunable nanoporous system featuring enhanced active surface area by stacking of spheres in cylindrical pores is fabricated. Highly ordered arrays of straight, constricted pores are obtained by anodization of metallic aluminum. Polystyrene (PS) spheres are assembled inside the pores by flowing their suspension through the porous membrane, whereas the construction serves as a filter. After surface functionalization with a noble metal catalyst, these model electrocatalysis systems exhibit functional properties (capacitance in electrochemical impedance spectroscopy) that mirror their geometric parameters. A systematic investigation of the system's geometry as it depends on the surface chemistry of the pores, on the one hand, and the physical parameters of the infiltration procedure, on the other hand, shows that mechanical stacking prevails over surface chemical interactions to determine the stacking density. The highest values of surface area are obtained when PS spheres are put in contact with HfO2 followed by ZnO according to adsorption measurements. Surface derivatization with organic layers does not improve stacking any further. However, choosing the proper concentration of PS spheres and flow rate are crucial for obtaining densely packed sphere assemblies without clogging of the pore entrance.
CRIS-Team Scopus Importer:2023-08-25
Keywords: anodic aluminum oxide; assembly; impedance spectroscopy; nanostructured electrodes; surface area

Sodium aluminates obtained from the Al(NO3)3 • 9H2O — NaOH system using the controlled precipitation method - Ruiz Madronero, Christhy; et al. (Revista Ingenieria E Investigacion, 2010)
Sodium aluminate, NaAlO2• xH2O, is an important comercial chemical used in water treatment, as a source of aluminium in the preparation of zeolites and other catalytic materials and as an additive in paper manufacturing. Sodium aluminates were synthesised in this work by using the Al(NO3)3 • 9H2O- NaOH system’s controlled precipitation method. Using the controlled precipitation method enabled identifying the process’s different stages from potentiometric titration of Al(NO3)3 • 9H2O dissolved in water and using NaOH as precipitating agent to ensure control and reproducibility and also identify final product characteristics. Powders were characterised by infrared spectroscopy (FTIR), X-ray diffraction (XRD) and gravimetric and differential thermal analysis (GDTA). The results indicated that NaAlO2 crystallised well at 1000°C (obtained as the main crystalline sodium aluminate phase) and that β-alumina treatment began to form at 1500°C. <br
Keywords: sodium aluminate; synthesis; controlled precipitation method.

Structural Analysis and Conduction Mechanisms in Polycrystalline Zinc Hydroxide Nitrate - Ruiz Madronero, Christhy; et al. (Inorganic Chemistry, 2018)
The conduction and dielectric properties in zinc hydroxide nitrate (Z5HN) were studied in detail as a function of the temperature and relative humidity by impedance spectroscopy, and the structure was investigated by X-ray diffraction (XRD). Elemental analysis indicated a layered material containing carbonate anions [Zn5(OH)8(NO3)1.6(CO3)0.2·1.7H2O] due to the high capability of adsorption of Z5HN, which makes this material appropriate for applications in real conditions. The water content affected the interlayer distance, conductivity, and dielectric response of the layered material. An electrostatic repulsive interaction after reduction of the water content as a function of the temperature causes an increase of the interlayer distance and a decrease in the conductivity response and dielectric behavior. The highest conductivity, 10−7 Ω−1 cm−1 , was obtained at a shorter interlayer distance for the sample heat-treated at 25 °C. The Z5HN synthesized was also characterized at different temperatures using thermogravimetric analysis and Fourier transform infrared and Raman spectroscopy. Multipeak analysis of the XRD patterns at various relative humidity levels showed the formation of a most hydrated phase and an increase of the interlayer distance related with the adsorption of water molecules. This layered material presented a conductivity of 10−5 Ω−1 cm−1 at high relative humidity (92%). The dipole−dipole interaction appeared to be the dominant mechanism for the dielectric behavior at the lowest temperatures and highest humidity due to the high water content in the Z5HN structure. Taking into account its crystallization water and high adsorption of water molecules in the interlayer region, a conduction pathway in the Z5HN structure was proposed, which provides the route for proton transport by hydrogen-bonding networks on the basis of a Grotthuss-type mechanism in facilitating the long-range proton hopping at 25 °C. The results for high relative humidity imply that a vehicular conduction mechanism also may contribute to the electrical response.<br

Structural, Thermal, and Release Properties of Hybrid Materials Based on Layered Zinc Hydroxide and Caffeic Acid - Ruiz Madronero, Christhy; et al. (Nanomaterials, 2020)
Caffeic acid (CA) molecules were immobilized in a layered inorganic host matrix based on zinc hydroxide structures with different starting interlayer anions, nitrate, and acetate. The chemical composition, structure, thermal stability, morphology, and surface of the host matrices and hybrid compounds were analyzed by X-ray diffraction (XRD), themogravimetric/differencial thermal analysis (TG/DTA), Fourier transform infrarred spectroscopy (FT-IR), scanning electron microscopy (SEM), and X-ray photoelectron spectroscopy (XPS). Additionally, the surface charge of the materials was investigated using zeta potential at pH 7. The results show an influence of the surface charge on the chemical, interaction, and structure of the resulting hybrid materials as a function of the starting layered structures. An expansion of the basal spacing to 10.20 Å for zinc hydroxide nitrate (ZHN), and a shrinkage to 10.37 Å for zinc hydroxide acetate (ZHA). These results suggest that the CA lies with a tilt angle in the interlayer region of the inorganic host matrix. The immobilization of CA is favored in ZHN, with respect to ZHA, because a single-layered phase was identified. A higher thermal stability at 65 °C was observed for ZHN-CA than for ZHA-CA. The evaluation of the release behavior showed a higher percentage of CA released from ZHN than ZHA, and the release mechanism was described by the Elovich model. The hybrid materials show potential characteristics for use as bioactive delivery systems.<br
Keywords: layered zinc hydroxide; caffeic acid; hybrid material; release systems; immobilization

The effect of the content of sodium in the obtaining of Na- β alúmina utilized the polymeric precursor method - Ruiz Madronero, Christhy; et al. (Dyna-Colombia, 2011)
In this work was utilized the Polymeric Precursor method to synthesis ceramic powders of Na + β alumina. We were interested in determinate the initial quantity from sodium precursor and its effect on crystalline phase obtained. Powders obtained were characterized using Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and Scanning Electron Microscopy (SEM). The effect of the initial quantity of sodium in the sample was very important in the nature of the final product. If we used one stoichiometric quantity of NaOH, to obtain NaAl11O17 compound, we obtained α-alumina as finish product (1450ºC). On the other hand, β alumina and/or Na2Al2xO3x-1 were obtained in samples thermal treatment from 1000ºC to 1350ºC. When we used a higher quantity of NaOH, sample nonstoichiometric, a solid with NaAl11O17 as majority phase was obtained. <br
Keywords: Na +β alumina; stoichiometric; nonstoichiometric; polymeric precursor.

Tm,Ho:KY(WO4)2 planar waveguide laser - Ruiz Madronero, Christhy; et al. (Laser Physics Letters, 2016)
A lattice-matched, 5 at.% Tm, 0.5 at.% Ho-codoped, 5.77 µm-thick KY0.58Gd0.22Lu0.20(WO4)2 active layer with optimized refractive index contrast is grown by liquid phase epitaxy on the (3 1 0) face of pure KY(WO4)2 substrate. Laser operation at 2051 nm (5I7 → 5I8 transition of the Ho3+ ion) is demonstrated with this waveguide pumped at 794 nm. The maximum continuous wave output power amounts to 1.9 mW at 2051 nm corresponding to a slope efficiency of 10.5%. The laser threshold is as low as 1.5 mW of absorbed pump power. The developed structure is promising for single-transverse-mode channel holmium waveguide lasers. Laser operation in 3 at.% Tm-singly doped 4.41 µm thick layer grown on the (3 1 0)-oriented substrate is also demonstrated at 1841 nm with a slope efficiency of 31%.<br
Keywords: waveguide lasers; holmium; thulium; double tungstates